Determination of Anthocyanin Levels in Telang Flower (Clitoria Ternatae) Using the Differential pH Method Based on Three Types of Solvents - Ramdan, Siti Rahmah Kurnia; Wulandari, Risda (JURNAL KESEHATAN STIKes MUHAMMADIYAH CIAMIS, 2023)
Anthocyanins are pigments that are soluble in polar solvents naturally and belong to the flavonoid group found in various types of plants. As the name implies, this pigment gives color to the flowers, fruit, and leaves, and has been widely used as a natural colorant in various food products and other applications. Telang flower is an example of a plant that has high levels of anthocyanins. The research method to prepare the test sample used was extraction by maceration using 3 types of solvents ethanol 96%, n-butanol and ethyl acetate. The test was carried out using the differential pH method using UV-Vis spectrophotometry at 510 nm and 700 nm. The assay results obtained were the average anthocyanin content of telang flower extract in ethanol 96% 0,946%, n-butanol 1,684%, ethyl acetate 0,181%. The results of data analysis showed that all the average levels of telang flower extract from each solvent were different, in other words the average levels of telang flower extract from each solvent were significant differences. The highest anthocyanin levels in this study were produced in the telang flower extract with n-butanol as a solvent of 1,684% and the lowest in the telang flower extract with ethyl acetate solvent of 0,181%.